(untitled) (Journal of the College of Basic Education, 2022)
The problem of the current research is to answer the following questions: What is the level of obedience behavior among the first grade pupils enrolled and not enrolled in kindergartens? Is worship behavior different according to sex? The importance of the current research lies in considerations that can be summarized as follows the importance of enrollment in kindergartens because this stage is the basis for the formation of the personality of the individual future. This topic is a scientific contribution focused in the attempt to prepare children distinguished by achieving natural behavior away from the stubborn behavior of the class The first is for each child to be an active member of the community. The current research aims at identifying the behavior of the students in the first grade of primary school enrolled and not enrolled in kindergartens and the recognition of the behavior of the students in the first grade of primary enrollment and not enrolled in kindergartens according to the sex variable (male - female). The current research is determined by the first grade students enrolled and not enrolled Kindergartens and both sexes for the academic year 2018-2019. The study sample consisted of (50) students and students (25) students and students enrolled in kindergartens and (25) students and students from others enrolled in kindergartens. The sample was chosen in a simple random way. Two schools were chosen from the General Directorate for the education of Baghdad. The test is the test of two independent test scores among first grade students who are enrolled and not enrolled in kindergartens. CONCLUSIONS: Based on the findings of the two researchers, Miley concluded:Students who are enrolled and not enrolled in Riyadh are characterized by the behavior of the club. Weakness of the attention of the teachers in the stage of kindergartens who are characterized by the behavior of the club and how to treat it.. The lack of teachers in the stage of kindergarten to skills dealing with children who are characterized by atheistic behavior